1H HRMAS NMR Metabolomics for the Characterization and Monitoring of Ripening in Pressed-Curd Ewe’s Milk Cheeses Produced Through Enzymatic Coagulation - David Castejón; José Segura; Karen P. Cruz-Díaz; María Dolores Romero-de-Ávila; María Encarnación Fernández-Valle; Víctor Remiro; Palmira Villa-Valverde; María Isabel Cambero (Foods, 2025)
A comprehensive characterization of two pressed-curd cheeses produced from ewe’s milk using enzymatic coagulation—Manchego cheese (with Protected Designation of Origin, PDO) and Castellano cheese (with Protected Geographical Indication, PGI)—was performed throughout the manufacturing process (industrial or traditional) and ripening stages (2, 9, 30, 90, and 180 days). Proton high-resolution magic angle spinning nuclear magnetic resonance (1H HRMAS NMR) spectroscopy, combined with Principal Component Analysis (PCA) and cluster analysis, was applied to intact cheese samples. The combination of this spectroscopic technique with chemometric methods allows for the characterization of each type of sheep milk cheese according to its geographical origin and production method (artisanal or industrial), as well as the estimation of ripening time. The results demonstrate that HRMAS NMR spectroscopy enables the rapid and direct analysis of cheese samples, providing a comprehensive profile of their metabolites—a metabolic ‘fingerprint’.